Peningkatan Skill Wirausaha Siswa Melalui Pembuatan Sabun Cair Bebas Alergen Mengandung Minyak Atsiri Limbah Kulit Jeruk Nipis Di SMA Labschool, Banda Aceh - Poppy Anjelisa Zaitun Hasibuan; Muhammad Fauzan Lubis; Nurul Suci; Nur Aira Juwita; Didi Nurhadi Illian (Unri Conference Series: Community Engagement, 2025)
Secondary school students' entrepreneurial competencies frequently remain confined to theoretical understanding without practical application in economically viable products. Concurrently, lime (Citrus aurantifolia) peel waste, containing valuable antibacterial essential oils, is often discarded without optimal utilization. This community engagement initiative aimed to enhance students' entrepreneurial capabilities through training in producing hypoallergenic liquid soap derived from lime peel essential oil. The intervention employed a Community Based Interactive Approach (CBIA) methodology, implemented through three distinct phases: pre-implementation, implementation, and monitoring and evaluation. Analytical results demonstrated that the formulated liquid soap exhibited dermatologically favorable properties including a pH range of 5.0-6.8, viscosity between 1100-1285 cP, and stable foam height maintenance (5.5-6.5 cm). The product demonstrated moderate antibacterial efficacy against Staphylococcus aureus (9.75 mm inhibition zone) and Escherichia coli (6.88 mm inhibition zone). Hedonic evaluation revealed exceptionally positive consumer acceptance, with ≥80% of panelists expressing preference for the product's aroma, chromatic characteristics, and textural properties. Irritation assessment confirmed the product's dermatological safety. Most significantly, participants exhibited a substantial 54.5% improvement in entrepreneurial comprehension, with mean evaluation scores increasing from 55 (pre-test) to 85 (post-test). This program successfully augmented students' entrepreneurial competencies while providing an innovative solution for repurposing organic waste into commercially viable products.